Narrative Review: Nursing Interventions for Managing Anxiety and Depression in Acute Care Settings - Abutalib, Fatimah Haidar Hussein; Zailaey Ashwaq Naser; Anoud Ibrahim Ahmd Ahmdini; Nawal Ali Ali Awaji; Reham Abdu Abdallah Refaee; Kamlah Mahdi Mohammed Khardali; Sharifah Husain Yahya Dabash; Ahlam Ibrahim Shrahit; Muzainh Mohammed Abutalib (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Anxiety and depression are highly prevalent comorbidities in acute care settings, affecting up to 30-40% of inpatients. Despite their high prevalence and profound impact, these conditions are frequently under-recognized and sub-optimally managed within the fast-paced, biomedically focused environment of acute care units. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This narrative review aims to synthesize contemporary evidence on effective, nurse-led interventions for the screening, assessment, and management of anxiety and depression in adult patients within acute medical and surgical inpatient settings. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A comprehensive search of PubMed, CINAHL, PsycINFO, and the Cochrane Library was conducted for literature published between 2010 and 2024. Keywords included "acute care," "general hospital," "inpatient," "anxiety," "depression," "nursing interventions," "screening," and "management." <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Effective management is underpinned by systematic screening using validated tools like the GAD-2/7 and PHQ-2/9. Evidence supports a multi-modal approach: foundational therapeutic communication (active listening, validation); psychoeducation to demystify the illness experience; targeted psychological strategies (problem-solving therapy, behavioral activation, relaxation techniques); collaborative medication management; and structured family involvement. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Nurses are pivotal in mitigating the adverse effects of anxiety and depression in acute care. Moving from tacit to explicit, protocol-driven care requires empowering nurses with knowledge, skills, and systemic support. Integrating evidence-based psychosocial interventions into standard nursing practice is not an optional adjunct but an essential component of holistic, high-quality acute care that can improve patient experience, clinical outcomes, and healthcare efficiency.